Performance of grasses with cutting management under seasonal waterlogged conditions - DHAR, SHIVA; GUPTA, S D; SINGH, A; ARYA, R L (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was carried out during 1997-98 to 1999-2000 to study the performance of para grass [Brachiariamutica (Forsk.) Stapf} and aleman grass [Echinochloa polystachya (Kunth) Hitchc.] with 3 cutting management (2 cuttings in October and May, 3 cuttings in September, March and June and 4 cuttings in August, October, March and May) under waterlogged conditions at Jhansi During the year of establishment, yield of grasses were significantly lower than the yield in latter years. Significantly higher green fodder (26.7 tonnes/ha), dry-matter (5.7 tonnes/ha) and crude protein yields (405 kg/hal were recorded from aleman grass than para grass. These yields were significantly higher (26.8 tonnes/ha green fodder, 6 tonnes/ha dry matter and 393.3 kg/ha crude protein) with 4 cuttings compared with other cuttings management in different months. Aleman grass gave significantly higher yield with 4 cuttings than that with the 2 or 3 cuttings and it was also significantly higher than para grass at all cutting-management levels.